The Impact of Board, Audit Committee, and Internal Control Characteristics on Earnings Quality: Evidence from Chinese Manufacturing Listed Companies from 2015 to 2018 - Zhao, Jingru (2020)
This study investigates the influence of board, audit committees, and internal control characteristics on the quality of financial reporting in the Chinese manufacturing industry. Abnormal accruals, as the proxy for earnings manipulation, is assessed by applying the modified-Jones Model (1995). This paper collects Chinese manufacturing firms listed on the Shanghai Stock Exchange and Shenzhen Stock Exchange from 2015 to 2018. The results suggest that effective internal control systems could lower discretionary accruals and enhance the quality of financial reporting. Additionally, more independent members on the AC could reduce the degree of income-decreasing management. Moreover, firms with fewer board meetings have better quality earnings. However, there is no evidence to support the relationship between board size, board independence, CEO duality, and AC size with earnings quality. This paper provides implications for the design of appropriate corporate governance systems for listed firms.